Pengelompokan Kab/Kota di Sumatera Barat Berdasarkan Penggunaan Metode Kontrasepsi Jangka Panjang Menggunakan Algoritma K-Medoids - Alya, Rahmika (Universitas PGRI Semarang, 2025)
The increasing population in West Sumatra poses challenges in birth control. The Family Planning (FP) program addresses this through Long-Term Contraceptive Methods (LTCM) such as tubectomy, vasectomy, IUD, and implants. However, LTCM adoption remains uneven across districts/cities, limiting program effectiveness. This study aims to classify districts/cities in West Sumatra based on LTCM usage using the K-Medoids algorithm, which is more robust to outliers compared to K-Means. Secondary data were obtained from the 2024 SIGA BKKBN database on the number of reproductive-age couples (RAC) using LTCM. The analysis included outlier detection with boxplots, data standardization, and clustering using K-Medoids with Silhouette methods to determine the optimal cluster. The results revealed two clusters: one with 14 regions of low LTCM usage and another with 5 regions of higher usage. These findings indicate disparities in contraceptive adoption, highlighting the need for targeted policies to increase LTCM use in low-usage regions.